Study of the Combined Effect of Maternal Tobacco Smoking and Polygenic Risk Scores on Birth Weight and Body Mass Index in Childhood - Fuentes-Paez, Georgina; Escaramís, Geòrgia; Aguilar-Lacasaña, Sofía; Andrusaityte, Sandra; Brantsæter, Anne Lise; Casas, Maribel; Charles, Marie-Aline; Chatzi, Leda; Lepeule, Johanna; Grazuleviciene, Regina; Gützkow, Kristine B.; Heude, Barbara; et al. (Frontiers in Genetics, 2022)
Background: Maternal smoking during pregnancy has adverse health effects in the offspring, including lower birth weight and increased risk for obesity. These outcomes are also influenced by common genetic polymorphisms. We aimed to investigate the combined effect of maternal smoking during pregnancy and genetic predisposition on birth weight and body mass index (BMI) related traits in 1,086 children of the Human Early Life Exposome (HELIX) project. Methods: Maternal smoking during pregnancy was self-reported. Phenotypic traits were assessed at birth or at the age of 8 years. Ten polygenic risk scores (PRSs) per trait were calculated using the PRSice v2 program. For birth weight we estimated two sets of PRSs based on two different base GWAS summary statistics: PRS-EGG, which includes HELIX children; and PRS-PanUK, which is completely independent. The best PRS per trait (highest R2) was selected for downstream analyses, and it was treated in continuous or categorized in 3 groups. Multivariate linear regression models were applied to evaluate the association of the explanatory variables with the traits of interest. The combined effect was evaluated by including an interaction term in the regression models, and then, running models stratified by PRS group. Results: BMI-related traits were correlated among them, but not with birth weight. A similar pattern was observed for their PRSs. On average, the PRSs explained ~4% of the phenotypic variation, with higher PRS values related to higher trait values (p-value <5.55E-08). Sustained maternal smoking was associated with lower birth weight and higher BMI and related traits (p-value <2.99E-02). We identified a gene by environment (GxE) interaction for birth weight between sustained maternal smoking and the PRS-EGG in 3 groups (p-value interaction = 0.01), which was not replicated with the PRS-PanUK (p-value interaction = 0.341). Finally, we did not find any statistically significant GxE interaction for BMI related traits (p-values interaction >0.237). Conclusion: Sustained maternal smoking and the PRSs were independently associated with birth weight and childhood BMI-related traits. There was low evidence of GxE interactions, except for birth weight, but further validation would be required.